Is the construction of a sanitary landfill acceptable in a karstic area? The case of the sanitary landfill site in Fokida, Central Greece - Soulios, G.; Mattas, C.; Kaklis, T.; Sotiriadis, M.; Voudouris, K.; Dimopoulos, G. (Bulletin of the Geological Society of Greece, 2013)
This paper investigates the suitability of a specific site for the construction of a sanitary landfill. The following works were performed: detailed geological mapping at a scale of 1:5,000, a geological-hydrogeological cross-section of the sanitary landfill, drilling exploration including the construction of a deep borehole for the detection of any perched aquifer, core logging and in situ permeability tests, implementation of the DRASTIC and EPIC methods to estimate the aquifer’s vulnerability. Finally estimation of the total annual amount of solid waste that will be deposited into the sanitary landfill and determination of the pollution load.